Effects of co-loaded doxorubicin and thymoquinone calcium carbonate nanoparticles on MDA MB231 breast cancer stem cells - Muibat, Ibiyeye Kehinde (2019)
A subtype of cells, cancer stem cells (CSCs) within the breast cancer has been implicated for the metastasis, chemo/radiotherapy resistance and relapse resulting in poor prognosis. The main objective of the study was to determine the effects of drugs- loaded (thymoquinone, doxorubicin, and a combination of thymoquinone and doxorubicin-loaded) aragonite CaCO3 nanoparticles (ACNP) on breast cancer stem cells. The formulated blank and drugs-loaded nanoparticles were characterized for physicochemical properties. The cytotoxic effect of blank and drug-loaded nanoparticles on MDA MB231 breast cancer cell line, 3D mammosphere, normal breast cells (MDF10A) and normal fibroblast (3T3) were also analysed. Morphological changes, sphere forming assay, cancer stem cell self-renewal capacity, ALDH activity analysis, CD44 and CD24 expression were carried out. The prepared nanoparticles were pleomorphic with sizes ranging from 53.65±10.29nm to 60.49±11.36nm and overall negative charge. The encapsulating efficiency of Dox and TQ in the dual loaded nanoparticles was found to be 95.8 and 41.6% respectively. The XRD patterns revealed strong crystallizations in blank and drug loaded formulation, while FTIR showed little alteration upon loading Dox and TQ. About 100% of drug release was noticed at pH 4.8, 70% at pH 6 while only 50% at pH 7.4. The blank nanoparticle was biocompatible, cell viability of 80% at a high concentration of 1000ug/ml. MDA MB231 IC50 dosages of drug-loaded nanoparticle were not toxic to the normal cells. For monolayer culture, the combination therapy showed enhanced apoptosis, reduction in cellular migration and invasion when compared to the single drug loaded nanoparticle and the free drugs. Scanning electron microscopy and transmission electron microscopy showed presence of cell shrinkage, cell membrane blebbing and disruption of cell membrane. For cancer stem cell enriched mammosphere, the combination therapy showed enhanced apoptosis, reduction in ALDH activity and expression of CD44 and CD24 surface maker, reduction in cancer stem cells metastatic capacity, inhibition of 3D sphere formation and cancer stem cell self-renewal capacity when compared to the free drugs and the single drug loaded nanoparticle. Scanning electron microscope showed poor spheroid formation, cell membrane blebbing, presence of cell shrinkage, distortion in the spheroid architecture. Thus, the cockle shell-derived aragonite calcium carbonate nanoparticle system provides a simple and efficient platform for multiple drug delivery and pH sensitive release. The combined drugs-loaded cockle shell-derived aragonite calcium carbonate nanoparticles (Dox/TQ-ACNP) showed higher efficacy in MDA MB231 breast cancer cells at lower dose of doxorubicin or thymoquinone, efficiently destroyed the breast CSCs and may be a potential curative strategy for the management of breast cancer recurrence and metastasis.